2018
DOI: 10.1161/circulationaha.117.029457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Aortic Dissection Detection Risk Score Plus D-Dimer for Acute Aortic Syndromes

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02086136.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
185
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(201 citation statements)
references
References 26 publications
4
185
3
9
Order By: Relevance
“…D‐dimer has been considered a sensitive but nonspecific marker for AAD. However, recent retrospective7 and prospective10 studies showed that if used in combination with an aortic dissection risk scoring system, D‐dimer testing has negative predictive values as high as 98.9%7 and 99.7%10 in patients with AAD. We believe such a combination of tests will become the standard diagnostic approach used to confirm or rule out AAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D‐dimer has been considered a sensitive but nonspecific marker for AAD. However, recent retrospective7 and prospective10 studies showed that if used in combination with an aortic dissection risk scoring system, D‐dimer testing has negative predictive values as high as 98.9%7 and 99.7%10 in patients with AAD. We believe such a combination of tests will become the standard diagnostic approach used to confirm or rule out AAD.…”
Section: Discussionmentioning
confidence: 99%
“…D‐dimer is now commonly measured not only following fibrinolytic therapy but also in the diagnosis of various diseases, including pulmonary embolism, disseminated intravascular coagulation, sepsis, malignancy, and acute myocardial infarction 4, 5. The utility of D‐dimer assessment in the diagnosis of acute aortic syndrome, including AAD, is well recognized 6, 7, 8, 9, 10. The European Society of Cardiology Guidelines recommends D‐dimer elevation as a IIa indication for a diagnostic workup of acute aortic syndrome,11 and previously reported studies have shown correlation between D‐dimer concentrations and the extent of aortic dissection 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, strict monitoring of the D‐dimer level may be valuable for determining potentially fatal evolution. D‐dimer >500 ng/mL is highly sensitive for ruling out classic acute aortic dissection within the first 6 hours after symptom onset, and <500 ng/mL may be found in patients with IMH . Additionally, the negative correlation between diabetes and aortic aneurysms is well described, and patients with diabetes have a reduced prevalence of thoracic and abdominal aortic aneurysms .…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer >500 ng/mL is highly sensitive for ruling out classic acute aortic dissection within the first 6 hours after symptom onset, and <500 ng/mL may be found in patients with IMH. 32,33 Additionally, the negative correlation between diabetes and aortic aneurysms is well described, and patients with diabetes have a reduced prevalence of thoracic and abdominal aortic aneurysms. 34,35 Is tight glycemic control still necessary for IMH patients since diabetes is probably a protective factor?…”
Section: Predictors Of Aorta-related Mortalitymentioning
confidence: 99%
“…Ascending AAD occurs most commonly between 50 and 60 years of age. In the 2010 guidelines, the American Heart Association and the American College of Cardiology introduced the aortic dissection detection risk score (ADDRS) as a simple and systematic bedside tool guiding the diagnostic approach to suspected AAD that was revised in 2017 including the D‐dimer assay. Hereby, we present a 64‐year‐old patient with a typical atrial fibrillation (AF)—a condition actually nonincluded into the ADDRS—masking an AAD Stanford type‐A extended into the right coronary artery (RCA) originating from the aortic false lumen, axillary artery aneurysm, and thrombosis.…”
Section: Introductionmentioning
confidence: 99%